Serum Magnesium and Calcium Status among Term Asphyxiated Newborns with Moderate to Severe Hypoxic-ischemic Encephalopathy (HIE) (Journal of Dhaka Medical College, 2018)
Background & objective: Perinatal asphyxia affects all organs of the body and brain is the most affected organ. The study was undertaken to find out the status of serum magnesium and calcium level and their significant association among asphyxiated term newborns with moderate to severe HIE.Material & methods: The Cross sectional study was done in the Department of Neonatology, Dhaka Medical College Hospital during January 2012 to July 2012. A total of 102 asphyxiated term neonates were enrolled , who has H/O perinatal asphyxia and had Apgar score of 6 or